The Effect of Group Activity Therapy on Improving Self-Esteem among Patients with Mental Disorders at Mutiara Sukma Mental Hospital, West Nusa Tenggara - Sugianto, Lalu Edi; Fathurrahman (Gema Cendekia Institute, 2026)
Low self-esteem is one of the most prevalent psychosocial problems among individuals with mental disorders and is closely associated with impaired social functioning, decreased motivation, and delayed recovery. Patients experiencing low self-esteem often exhibit withdrawal behaviors, reduced participation in therapeutic activities, and negative self-perception, which may further worsen their clinical condition. Therefore, effective psychosocial nursing interventions are essential to enhance patients’ self-concept and support holistic recovery. One such intervention is Group Activity Therapy (GAT), which facilitates interaction, emotional expression, and peer support within a structured group setting. This study aimed to examine the effect of Group Activity Therapy on self-esteem among patients with mental disorders at Mutiara Sukma Mental Hospital, West Nusa Tenggara, Indonesia. A quasi-experimental study with a one-group pretest–posttest design was conducted involving 30 participants selected using purposive sampling. Self-esteem was measured using the Rosenberg Self-Esteem Scale (RSES), which demonstrated good reliability (Cronbach’s α = 0.82). Data were analyzed using the Shapiro–Wilk test to assess normality and paired sample t-test to evaluate differences before and after the intervention. Effect size was calculated using Cohen’s d. The results showed a statistically significant improvement in self-esteem scores, with the mean increasing from 18.40 ± 3.25 at baseline to 24.90 ± 3.10 after the intervention (p < 0.001). The effect size was large (Cohen’s d = 1.89), indicating a substantial clinical impact. These findings suggest that Group Activity Therapy is an effective psychosocial intervention to improve self-esteem among patients with mental disorders. Integrating GAT into routine psychiatric nursing care may enhance psychosocial rehabilitation outcomes and contribute to more comprehensive mental health services.